Biofilms and antibiotic resistance profile of Enterococcus faecalis in selected dairy cattle farm environments in Bangladesh - Naeem Ahammed Ibrahim Fahim; Md. Liton Rana; Md Abdullah Evna Hasan; Samia Salam; Rony Ibne Masud; Nazmul Huda; Sukumar Saha; Md. Tanvir Rahman (PLoS ONE, 2025)
Enterococci are opportunistic zoonotic pathogens. Dairy cattle and farm environments are considered important sources of Enterococcus spp. Here, we detected biofilm-forming Enterococcus faecalis circulating in dairy cattle and farm environments, followed by the detection of their virulence genes, antibiogram phenotype analysis, and genotype characterization. Isolates were cultured and identified by PCR. Ability to biofilm formation was assessed using the Congo red agar test., followed by a disk diffusion test for antibiogram and PCR for virulence and resistance genes detection. Among 150 samples collected from 12 farms, 145 were culture-positive for Enterococci. Among these, 74 were PCR screened, of which 54.05% (40/74, CI 95%: 42.78–64.93) were E. faecalis. About 50% of E. faecalis isolates were strong biofilm formers, 37.5% were intermediate, and 12.5% were weak biofilm formers. In the antibiogram study, 87.5% of isolates were resistant to rifampicin, 75% to erythromycin, 67.5% to vancomycin, and 62.5% to ampicillin. Of the positive isolations of E. faecalis, 80% were positive for the vanA gene, and 50% were positive for the blaTEM resistance gene. Surprisingly, about 70% (28/40) of isolates showed a multidrug resistance phenotype. The Highest levels of multidrug-resistant E. faecalis were present in manure (87.5%) and isolates from Ullapara, Sirajganj. In PCR, 83.33%, 87.50%, 92.67%, 75%, 87.50%, and 58.33% isolates were positive for virulence genes agg, ace, pil, fsrA, fsrB, and gelE. This study marks the first investigation in Bangladesh focused on the molecular identification of biofilm-forming, multidrug-resistant strains of E. faecalis from dairy cattle and farm environments. We recommend implementing a One Health approach with the adoption of effective biosecurity and good farm management to monitor this multi-drug-resistant (MDR) E. faecalis in dairy cattle and farm environments, aiming to effectively tackle the critical challenge of antimicrobial resistance.